Pathogenicity and Interspecies Transmission of Cluster 3 Tembusu Virus Strain TMUV HQ-22 Isolated from Geese - Qing Yang; Yingying Ding; Weiping Yao; Shuyue Chen; Yaqian Jiang; Linping Yang; Guangbin Bao; Kang Yang; Shinuo Fan; Qingqing Du; Qing Wang; Guijun Wang (Viruses, 2023)
Since 2010, the Tembusu virus (TMUV) has been highly prevalent in China, causing significant economic losses to the poultry industry. In 2022, a suspected outbreak of TMUV occurred at a goose farm located in Anhui Province. A strain of TMUV, TMUV HQ-22, was isolated from the infected geese. Phylogenetic analysis using the E gene of the HQ-22 strain demonstrated its affiliation with cluster 3, a less commonly reported cluster in comparison to the main circulating cluster, cluster 2. Through a comparison of the envelope (E) protein of HQ-22 with other typical TMUV strains, a mutation at the 157th amino acid position was identified, wherein valine (V) in cluster 3 changed to alanine (A), a characteristic that is unique to cluster 2. These findings highlight the diversity and complexity of the TMUV strains circulating in China. In our experimental analysis, an injection of TMUV HQ-22 into the muscles of 3-day-old goslings resulted in severe neurological symptoms and a mortality rate of 60%. Similarly, the intracranial or intranasal infection of 3-week-old ICR mice with TMUV HQ-22 led to severe neurological symptoms and respective mortality rates of 100% or 10%. In summary, our study isolated a TMUV strain, TMUV HQ-22, from geese that belongs to cluster 3 and exhibits significant pathogenicity in both goslings and ICR mice. These results emphasize the genetic diversity of the TMUV circulating in China and expand the host range beyond mosquitoes to include ducks, chickens, geese, and even mice. It is crucial to not underestimate the risk of TMUV infection in mammals, warranting our utmost attention.